MODEL PENGEMBANGAN TEKNIK DAN POLA ANYAM SEBAGAI STRUKTUR DASAR KARYA SENI RUPA EKSPRESI - Rohandi, Teten; Nagara, Martien Roos; Noor Zaman, Farid Kurniawan (Jurusan Seni Rupa ISBI Bandung, 2021)
Weaving patterns for craftsmen are molds for mass-producing products, while in fine art, patterns are used as the basic structure for the formation of a more expressive work. The focus of this research is the search for basic weaving techniques and patterns, whether based on tradition or the results of self-exploration which are used as the basic structure for the formation of works of art that are more subject to expression by exploring aesthetic values that are in the area of pure art science with the aim of developing fine arts. at the same time the art of traditional weaving, thus creating a novel pattern that has its own characteristics and increases the value of appreciation. Researchers used descriptive qualitative methods and went directly to the field in collecting data as material for analysis and interpretation. The results of the study were 5 pieces of artistic expression creation models based on weaving patterns commonly used by Tasikmalaya craftsmen. It is hoped that this research can be used as a reference as an alternative in creating fine arts that can be appreciated by a wide audience and provide inspiration as well as help preserve Indonesian traditional art. Keywords: exploration, weaving technique, weaving pattern, basic structure, artistic expression——————————————————————————————Pola anyam bagi perajin adalah cetakan untuk memproduksi produk secara masal, sedangkan dalam fine art, pola dijadikan sebagai struktur dasar pembentukan karya yang lebih ekspresif. Fokus penelitian ini adalah pencarian teknik dan pola anyam dasar, baik yang berpijak dari tradisi atau hasil eksplorasi sendiri yang dijadikan struktur dasar pembentukan karya seni rupa yang lebih bersifat ekspresi subjek dengan penggalian nilai estetik yang berada di wilayah keilmuan seni rupa murni dengan tujuan mengembangkan seni rupa sekaligus seni anyam tradisi, sehingga menciptakan pola baru yang memiliki ciri khas serta peningkatan nilai apresiasi. Peneliti menggunakan metode kualitatif deskriptif dan terjun langsung ke lapangan. Hasil penelitian berupa 5 buah model kreasi seni ekspresi berdasarkan pola-pola anyam yang biasa digunakan oleh perajin Tasikmalaya. Diharapkan penelitian ini dapat menjadi acuan sebagai alternatif dalam berkarya seni rupa yang dapat diapresiasi oleh khalayak luas dan memberi inspirasi sekaligus ikut melestarikan seni rupa tradisi Indonesia. Kata kunci: eksplorasi, teknik anyam, pola anyam, struktur dasar, karya seni rupa ekspresi